Impaired activity of CCA-adding enzyme TRNT1 impacts OXPHOS complexes and cellular respiration in SIFD patient-derived fibroblasts - Liwak-Muir, Urszula; Mamady, Hapsatou; Naas, Turaya; Wylie, Quinlan; McBride, Skye; Lines, Matthew; Michaud, Jean; Baird, Stephen D; Chakraborty, Pranesh K; Holcik, Martin (Université d'Ottawa | University of Ottawa, 2016)
Abstract Background SIFD (Sideroblastic anemia with B-cell immunodeficiency, periodic fevers, and developmental delay) is a novel form of congenital sideroblastic anemia associated with B-cell immunodeficiency, periodic fevers, and developmental delay caused by mutations in the CCA-adding enzyme TRNT1, but the precise molecular pathophysiology is not known. Results We show that the disease causing mutations in patient-derived fibroblasts do not affect subcellular localization of TRNT1 and show no gross morphological differences when compared to control cells. Analysis of cellular respiration and oxidative phosphorylation (OXPHOS) complexes demonstrates that both basal and maximal respiration rates are decreased in patient cells, which may be attributed to an observed decrease in the abundance of select proteins of the OXPHOS complexes. Conclusions Our data provides further insight into cellular pathophysiology of SIFD.